A late Pleistocene gastropod fauna from the northern Caspian Sea with implications for Pontocaspian gastropod taxonomy - Neubauer, Thomas A.; van de Velde, Sabrina; Yanina, Tamara; Wesselingh, Frank P.; Justus Liebig University Giessen (My University, 2018)
The present paper details a very diverse non-marine gastropod fauna retrieved from Caspian Pleistocene deposits along the Volga River north of Astrakhan (Russia). During time of deposition (early Late Pleistocene, late Khazarian regional substage), the area was situated in shallow water of the greatly expanded Caspian Sea. The fauna contains 24 species, of which 16 are endemic to the Pontocaspian region and 15 to the Caspian Sea. The majority of the species (13) belongs to the Pyrgulinae (Hydrobiidae), a group famous for its huge morphological variability in the Pontocaspian region. The phenotypic diversity has led to an inflation of genus and species names in the literature. New concepts are proposed for many of the genera and species found in the present material, with implications for the systematics and taxonomy of the entire Pontocaspian gastropod fauna. Laevicaspia vinarskii sp. n. is described as a new species. This contribution is considered a first step in revising the Pontocaspian gastropod fauna.
Keywords: biodiversity; endemism; long-lived lakes; non-marine Gastropoda; Quaternary; ddc:570